PROTOCOL: Understanding Intergenerational Programmes to Improve the Psychosocial Health and Well‐Being of Older Adults in Residential Aged Care: A Rapid Realist Review Protocol - Lysha Z. Y. Lee; Patricia Nicholson; Katrin Gerber; Ramona Naicker; Alison M. Hutchinson (Campbell Systematic Reviews)
ABSTRACT This is the protocol for a Campbell systematic review. The main objective of this realist review is to gather, critically appraise, and synthesize evidence to identify what works, for whom, in what circumstances, and how non‐familial intergenerational programs involving pre‐school children work to improve the psychosocial well‐being of older adults living in residential aged care settings.